Composite hydrogel as well as preparation method and application thereof
By developing a composite hydrogel composed of a carrier matrix and polymer microspheres loaded with metal ions or metal nanoparticles, the problem of anti-infection and promoting bone healing in the bone defect area is solved, achieving the sustained release of active ingredients and the application of multifunctional bone implant materials.
Patent Information
- Application Number
- CN202411865073.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
It is difficult to develop a multifunctional bone implant material that can resist infection in the bone defect area and promote bone healing, and can achieve sustained release of the active ingredient.
A composite hydrogel is used, which consists of a carrier matrix and polymer microspheres loaded with metal ions or metal nanoparticles, and is prepared by protease hydrolysis and mineralization to achieve sustained release of the active ingredient.
This composite hydrogel can effectively promote the antibacterial, osteogenic and immune regulation capabilities of the bone defect area, achieve sustained release of active ingredients, and is suitable for large-scale production.
Smart Images

Figure CN119701091A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite hydrogel and a preparation method and application thereof, belonging to the field of medical materials. Background Art
[0002] Bone tissue engineering, as a common method for bone defect regeneration and reconstruction, can avoid the disadvantages of donor limitation and potential immune rejection, and has significant advantages over autologous, homologous or artificial bone transplantation. However, bacterial infection and immune rejection in the defect area often lead to delayed or even failed bone healing. However, there are almost no materials that can solve the above problems and have good osteogenic activity at the same time. Therefore, there is an urgent need to develop a multifunctional bone implant material that can resist infection and promote bone healing.
[0003] In recent years, the important role of the immune system in osteogenesis has gradually attracted people's attention. During osteogenesis, the immune system and the skeletal system share a variety of cytokines, receptors, signaling molecules and transcription factors. Among them, macrophages, which have multiple effects on bone healing, are the main targets of regulating the immune phase. Macrophages are generally divided into two phenotypes, typically activated inflammatory macrophages (M1) and selectively activated inflammatory macrophages (M2). The M1 phenotype of macrophages is characterized by increased production of proinflammatory cytokines (TNF-α, IL-1β), which play a role in the early stages of the repair response. It can determine the subsequent behavior of immune cells by inhibiting inflammation and initiating tissue repair, or by amplifying the inflammatory response by destroying normal bone tissue. The M2 phenotype of macrophages produces a variety of anti-inflammatory cytokines (IL-10, TGF-β), promotes wound healing, and guides bone repair. The early immune microenvironment of bone tissue determines the outcome of bone regeneration. Therefore, for the treatment of bone defects, the focus of new ideas is to introduce functional drugs into implant materials to improve osteogenesis by promoting the polarization of macrophages from the M1 phenotype to the M2 phenotype.
[0004] At present, the most effective drugs for promoting macrophage polarization are the introduction of nutrients such as bioactive factors, inflammatory cytokines and metal ions. Among all drugs, different metal ions enter the physiological structure of the human body and play a functional role in the physiological environment of cells and in the process of bone healing. Therefore, the modification of biomaterials with metal ions has broad application prospects. The combination of metal ions and biomaterials is also widely used in material modification to improve the biological activity of biomaterials. However, there is still no good solution for how to introduce metal ions and make the metal ions play their full role.
[0005] Antibiotics such as tetracycline or vancomycin are commonly used clinically for bone defect area infections. However, systemic antibiotic treatment often leads to potential systemic toxicity and low penetration into wound necrotic tissue. These antibiotics have poor antibacterial properties against multidrug-resistant strains, which ultimately leads to failure of anti-infection treatment. Nanoparticles are considered to be a favorable choice to make up for the shortcomings of traditional antibiotic treatment due to their strong broad-spectrum antibacterial properties. However, the introduction of nanoparticles generally causes a burst release, resulting in their ineffective function and other problems.
[0006] As a key element of tissue engineering, scaffolds provide structural support and adhesion sites for the growth of cells and tissues, allowing cells to penetrate and release nutrients. In recent years, small intestinal submucosa (SIS), as a cell-free natural collagen extracellular matrix material, has been widely used in the repair and regeneration of soft tissues. SIS is mainly composed of type I and type III collagen, contains a small amount of type V and type VI collagen, and has good toughness. In addition, many cell growth factors such as basic fibroblast growth factor, vascular endothelial growth factor and transforming growth factor have been found in decellularized SIS. After implantation into the human body, the hydrogel prepared by SIS forms a 3D network, forming an extracellular environment similar to natural tissue, and retains the complete composition and biological activity of the extracellular matrix, providing a stable microenvironment for cell growth and promoting the formation of new tissues. However, if metal ions and nanoparticles are directly loaded in the hydrogel prepared by SIS, they will cause a sudden release, leading to other problems.
[0007] Therefore, developing a composite hydrogel that can promote the antibacterial, osteogenesis, and immunomodulatory capabilities of bone defects and achieve sustained release of active ingredients has become a technical problem that needs to be solved urgently. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] In view of the technical problems existing in the prior art, the present invention first provides a composite hydrogel that can promote the antibacterial, osteogenesis and immunomodulatory capabilities of bone defects and achieve the sustained release of active ingredients.
[0010] The present invention also provides a method for preparing the composite hydrogel. The preparation method is simple and easy to implement, the raw materials are easy to obtain, and the method is suitable for mass production.
[0011] Solutions for solving problems
[0012] [1] A composite hydrogel comprising:
[0013] A carrier matrix, wherein the carrier matrix is derived from a degradable biomaterial, and the degradable biomaterial contains collagen; and
[0014] polymer microspheres, the polymer microspheres being loaded on the surface and / or inside of the carrier matrix; and,
[0015] The polymer microspheres have active ingredients on their surfaces and / or inside, and the active ingredients include metal ions and / or metal nanoparticles.
[0016] [2] The composite hydrogel according to [1] above, wherein the carrier matrix is obtained by hydrolyzing the degradable biomaterial with a protease; preferably, the degradable biomaterial contains collagen, and more preferably, the degradable biomaterial contains small intestinal submucosal material.
[0017] [3] The composite hydrogel according to [1] or [2] above, wherein the average particle size of the polymer microspheres is 1-100 μm;
[0018] Preferably, the polymer microspheres are derived from one or a combination of two or more of gelatin microspheres, polylactic acid microspheres, polycaprolactone microspheres, polyglycolic acid microspheres, polymethyl methacrylate microspheres, and polylactic acid-glycolic acid copolymer microspheres.
[0019] [4] The composite hydrogel according to any one of [1] to [3] above, wherein the content of the polymer microspheres is 0.001-0.1 mg / mL based on the total volume of the carrier matrix.
[0020] [5] The composite hydrogel according to any one of [1] to [4] above, wherein the metal ions include one or a combination of two or more of strontium ions, magnesium ions, copper ions, iron ions and zinc ions;
[0021] The metal nanoparticles include one or a combination of two or more of silver nanoparticles, gold nanoparticles, copper nanoparticles, and iron nanoparticles.
[0022] [6] A method for preparing a composite hydrogel according to any one of [1] to [5] above, comprising the step of loading polymer microspheres on the surface and / or inside of a carrier matrix;
[0023] Preferably, the preparation method comprises the following steps:
[0024] The degradable biomaterial is hydrolyzed by protease to obtain a pre-gel;
[0025] Adjusting the pH value of the pregel to 6-8 to allow the pregel to self-assemble to obtain a gel product;
[0026] Performing mineralization treatment on the polymer microspheres to obtain mineralized microspheres;
[0027] The surface and / or interior of the mineralized microspheres are provided with active ingredients, wherein the active ingredients include metal ions and / or metal nanoparticles, to obtain functionalized microspheres;
[0028] The functionalized microspheres are mixed with the gel product and incubated to obtain a composite hydrogel.
[0029] [7] The preparation method according to [6] above, wherein the hydrolysis treatment time is 6-18 hours. Preferably, before the hydrolysis treatment, it also includes a step of washing the degradable biomaterial with a detergent.
[0030] [8] The preparation method according to [6] or [7] above, wherein the mineralization treatment comprises using simulated body fluid to mineralize the polymer microspheres to obtain mineralized microspheres; more preferably, the mineralization treatment time is 6-18 hours and the mineralization treatment temperature is 35-40°C.
[0031] [9] The preparation method according to any one of [6] to [8] above, wherein the mineralized microspheres are immersed in a functionalization solution for functionalization treatment, so that the surface and / or interior of the mineralized microspheres have active ingredients, and the active ingredients include metal ions and / or metal nanoparticles, to obtain functionalized microspheres; wherein the functionalization solution includes metal salts and / or metal nanoparticles; preferably, the immersion time is 2-6 hours;
[0032] More preferably, in the functionalized solution, the mass concentration of the metal salt is 0.0005-0.1%, and the mass concentration of the metal nanoparticles is 0.0005-0.1%.
[0033]
[10] Use of the composite hydrogel according to any one of [1] to [5] above for preparing bone repair materials.
[0034] Effects of the Invention
[0035] The composite hydrogel of the invention can promote the antibacterial, osteogenesis and immunoregulatory capabilities of bone defects and can achieve a sustained release effect.
[0036] The preparation method of the composite hydrogel of the invention is simple and easy, the raw materials are easy to obtain, and it is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The surface morphology of the mineralized PLGA microspheres of Example 1 of the present invention is shown.
[0038] Figure 2 The surface morphology and EDS image of the PLGA-Ag-Sr microspheres of Example 1 of the present invention are shown.
[0039] Figure 3 SEM images of the composite hydrogel containing microspheres on different surfaces of Example 1 of the present invention are shown, wherein the red arrows indicate the PLGA microspheres.
[0040] Figure 4 The Ag content of the composite hydrogel in Example 1 of the present invention is shown in FIG. + and Sr 2+ release curve.
[0041] Figure 5 A schematic diagram of the biocompatibility of the composite hydrogel is shown; wherein,
[0042] A shows the live / dead staining of bone marrow mesenchymal stem cells and mouse macrophages;
[0043] B shows the proliferation ability of the composite hydrogel of the present invention on bone marrow mesenchymal stem cells and mouse macrophages.
[0044] Figure 6 A schematic diagram of the in vitro antibacterial activity of the composite hydrogel is shown; wherein,
[0045] A shows the SEM image of bacteria on the sample extract;
[0046] B shows the detection of total antimicrobial activity;
[0047] C shows the quantitative analysis of bacterial colonies;
[0048] D shows the bacterial inhibition zone after co-culture with sample extracts for 24 hours, where (a): blank control, (b): PA-SIS, (c): PS-SIS, (d): P-AS-SIS.
[0049] Figure 7 A schematic diagram of live / dead staining of cells is shown, where green represents live bacteria and red represents dead bacteria;
[0050] A shows a live / dead staining schematic of Staphylococcus aureus;
[0051] B shows a schematic diagram of live / dead staining of E. coli.
[0052] Figure 8 The effect of composite hydrogel on the expression of osteogenic-related factors of bone marrow mesenchymal stem cells is shown;
[0053] A shows qRT-PCR analysis of osteogenesis-related genes;
[0054] B shows immunoblot analysis of osteogenesis-related proteins;
[0055] C shows the quantitative analysis of immunoblot analysis;
[0056] D shows alkaline phosphatase and Alizarin Red S staining of bone marrow mesenchymal stem cells.
[0057] Fig. 9 The immunofluorescence analysis of the localization of osteogenic related proteins in bone marrow mesenchymal stem cells is shown (osteogenic related proteins: green, cell nucleus: blue); wherein,
[0058] A shows immunofluorescence analysis of bone morphogenetic protein-2;
[0059] B shows immunofluorescence analysis of alkaline phosphatase.
[0060] Fig.10 Shows the response of mouse macrophages to sample extracts and Sr 2+ Effects on macrophage polarization process; among them,
[0061] A shows confocal laser scanning microscopy (CLSM) images of mouse macrophages after culturing on different samples for 3 days;
[0062] B shows the expression levels of pro-inflammatory and anti-inflammatory genes related to mouse macrophages by qRT-PCR analysis after mouse macrophages were cultured on different samples for 3 days;
[0063] C shows immunofluorescence staining of inducible nitric oxide synthase and macrophage mannose receptor-1.
[0064] Fig.11 The evaluation of the repair effect of the composite hydrogel on infected skull defects is shown; wherein,
[0065] A shows the three-dimensional reconstruction image of new bone formation 3 months after surgery;
[0066] B shows the quantitative analysis of bone volume fraction in the defect;
[0067] C shows a schematic diagram of the staining results of hematoxylin-eosin;
[0068] D shows a schematic diagram of the staining results of Masson's trichrome staining;
[0069] E shows a schematic diagram of the staining results of immunohistochemical staining; DETAILED DESCRIPTION
[0070] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0071] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0072] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0073] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0074] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0075] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0076] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.
[0077] In this specification, the abbreviations and symbols are shown in Table A below:
[0078] Table A
[0079]
[0080] <First aspect>
[0081] The first aspect of the present invention provides a composite hydrogel comprising:
[0082] A carrier matrix, wherein the carrier matrix is derived from a degradable biomaterial, and the degradable biomaterial contains collagen; and
[0083] polymer microspheres, the polymer microspheres being loaded on the surface and / or inside of the carrier matrix; and,
[0084] The polymer microspheres have active ingredients on their surfaces and / or inside, and the active ingredients include metal ions and / or metal nanoparticles.
[0085] Carrier Matrix
[0086] In the present invention, the carrier matrix is derived from a degradable biomaterial, and the degradable biomaterial includes collagen. The collagen can be natural, synthetic, modified or cross-linked, including but not limited to submucosal, dermal, pericardial, collagen, gelatin, etc.
[0087] In some embodiments of the present invention, the carrier matrix is derived from the small intestinal submucosa, preferably from the decellularized small intestinal submucosa, that is, the small intestinal submucosa can be used to prepare the carrier matrix of the present invention. In some embodiments of the present invention, the carrier matrix is derived from the dermis, preferably from the decellularized dermis, that is, the dermis can be used to prepare the carrier matrix of the present invention. In some embodiments of the present invention, the carrier matrix is derived from the bladder submucosa, preferably from the decellularized bladder submucosa, that is, the bladder submucosa can be used to prepare the carrier matrix of the present invention. In some embodiments of the present invention, the carrier matrix is derived from the pericardium, preferably from the decellularized pericardium, that is, the pericardium can be used to prepare the carrier matrix of the present invention. The submucosa (e.g., the small intestinal submucosa), dermis, pericardium, etc. are preferably derived from mammals, such as pigs, cattle, sheep, dogs, cats, etc.
[0088] In one embodiment of the present invention, the carrier matrix is derived from decellularized porcine small intestinal submucosa. The porcine small intestinal submucosa can be purchased commercially. The porcine small intestinal submucosa has a wide range of sources, is economical and easy to obtain, and is easy to process. The porcine small intestinal submucosa after decellularization has excellent biocompatibility, is rich in collagen and growth factors, can induce cells to diffuse, adhere, grow, and proliferate inward, and promote the repair and regeneration of the tissue defect's own tissue. It is suitable for use as a carrier matrix for preparing the biological patch of the present invention. Therefore, the present invention preferably uses the porcine small intestinal submucosa material prepared as a raw material as a carrier matrix.
[0089] The present invention does not specifically limit the preparation method of the porcine small intestinal submucosa material, and the preparation method may be some commonly used preparation methods in the art. Of course, the porcine small intestinal submucosa material may also be purchased commercially.
[0090] Specifically, the pig small intestine submucosal material of the present invention can be prepared by the following preparation method. The pig small intestine is cut into segments and the mesentery is peeled off, the mucosal layer and the serum membrane layer are mechanically scraped off to form a transparent film, and then defatting and decellularizing are performed to obtain the pig small intestine submucosal material. For the decellularization treatment, trypsin is generally used for treatment.
[0091] The inventors of the present invention have found that the main components of the pig small intestine submucosa material are type I and type III collagen, which has good biocompatibility and the prepared medical hydrogel has good physical properties. In addition, SIS contains a variety of active factors such as proteoglycans, elastin, glycosaminoglycans, growth factors, etc., which have a promoting effect on cell proliferation, etc. As the raw material of the hydrogel, the pig small intestine submucosa material can not only be used as a carrier for sustained release of Hst1; at the same time, it can promote the formation of epithelial attachment through mutual compensation of different signal pathways, and improve the sealing of the soft tissue around the implant.
[0092] Furthermore, in the present invention, the carrier matrix can be obtained by hydrolyzing the degradable biomaterial with protease, which is beneficial for preparing the composite hydrogel.
[0093] Polymer microspheres
[0094] The polymer microspheres of the present invention are loaded on the surface and / or inside of the carrier matrix; and the surface and / or inside of the polymer microspheres have active ingredients, and the active ingredients include metal ions and / or metal nanoparticles.
[0095] The present invention can achieve the effect of sustained release of active ingredients by using polymer microspheres. The present invention can further promote wound healing and guide bone repair by using active ingredients. Specifically, it can be achieved by improving the antibacterial properties of composite hydrogels, promoting macrophage polarization, and other aspects.
[0096] In some specific embodiments, the average particle size of the polymer microspheres is 1-100 μm, preferably 2-20 μm. When the average particle size of the polymer microspheres is 1-100 μm, they can better carry active ingredients.
[0097] Specifically, the polymer microspheres are derived from one or a combination of two or more of gelatin microspheres, polylactic acid microspheres, polycaprolactone microspheres, polyglycolic acid microspheres, polymethyl methacrylate microspheres, and polylactic acid-glycolic acid copolymer microspheres.
[0098] Furthermore, in order to most effectively exert the function of the active ingredient of the present invention, the metal ions include one or a combination of two or more of strontium ions, magnesium ions, copper ions, iron ions and zinc ions; the metal nanoparticles include one or a combination of two or more of silver nanoparticles (AgNPs), gold nanoparticles, copper nanoparticles and iron nanoparticles.
[0099] Furthermore, the active ingredient of the present invention may contain metal ions and metal nanoparticles, so that the functions of the metal ions and the metal nanoparticles can be effectively exerted.
[0100] In some specific embodiments, the content of the polymer microspheres is 0.001-0.1 mg / mL, preferably 0.005-0.05 mg / mL, based on the total volume of the carrier matrix. When the content of the polymer microspheres is 0.001-0.1 mg / mL, the carrier matrix can carry the polymer microspheres, so that the polymer microspheres can effectively play their role, which is more conducive to the sustained release of the active ingredient.
[0101] <Second Aspect>
[0102] The second aspect of the present invention provides a method for preparing the composite hydrogel according to the first aspect of the present invention, comprising the step of loading polymer microspheres on the surface and / or inside of the carrier matrix.
[0103] In some specific embodiments, the preparation method comprises the following steps:
[0104] The degradable biomaterial is hydrolyzed by protease to obtain a pre-gel;
[0105] Adjusting the pH value of the pregel to 6-8 to allow the pregel to self-assemble to obtain a gel product;
[0106] Performing mineralization treatment on the polymer microspheres to obtain mineralized microspheres;
[0107] The surface and / or interior of the mineralized microspheres are provided with active ingredients, wherein the active ingredients include metal ions and / or metal nanoparticles, to obtain functionalized microspheres;
[0108] The functionalized microspheres are mixed with the gel product and incubated to obtain a composite hydrogel.
[0109] Preparation of gel products
[0110] When the porcine small intestinal submucosal material is used as a degradable biomaterial, the preparation method of the porcine small intestinal submucosal material includes the following steps: cutting the porcine small intestine into segments and peeling off the mesentery, mechanically scraping off the mucosal layer and the serum membrane layer into a transparent film, and then performing a degreasing treatment to obtain a porcine small intestinal submucosal material (SIS), and then performing a degreasing treatment and a decellularization treatment on the porcine small intestinal submucosal material to obtain a decellularized porcine small intestinal submucosal material. For the decellularization treatment, trypsin is generally used for digestion.
[0111] Furthermore, in the present invention, the degradable biological material, such as the decellularized porcine small intestinal submucosa material, is hydrolyzed by protease to obtain the pre-gel.
[0112] In some specific embodiments, before hydrolysis, the degradable biomaterial can be placed in a detergent for washing, thereby facilitating the hydrolysis. Specifically, the degradable biomaterial can be washed with a mixed solution of sodium dodecyl sulfate and sodium chloride, and the washing time can be 2-10 hours, for example, 3 hours, 5 hours, 8 hours, etc.
[0113] Specifically, in the detergent, the mass concentration of sodium dodecyl sulfate is 0.01-1%, for example: 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9% and the like; the concentration of sodium chloride is 0.1-2%, for example: 0.3%, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9% and the like.
[0114] In addition, the present invention does not specifically limit the protease, which can be a protease commonly used in the art, such as pepsin, trypsin, etc. Specifically, the protease can be added to the washed product for hydrolysis treatment to obtain a pre-gel. Specifically, the hydrolysis time can be 12-48h, such as 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h, etc. The present invention does not specifically limit the amount of the protease, as long as the hydrolysis treatment can be completed.
[0115] Further, the pH value of the pregel is adjusted so that the pregel forms a gel product after self-assembly. Specifically, the pH value of the pregel can be adjusted to 6-8, for example: 6.5, 7, 7.5, etc., and then placed at a temperature of 35-40°C, for example: 36°C, 37°C, 38°C, 39°C, etc. for 10-60 minutes, for example: 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, etc., to obtain a gel product.
[0116] Preparation of functionalized microspheres
[0117] The present invention first obtains polymer microspheres. The polymer microspheres of the present invention can be prepared or purchased. The present invention does not specifically limit the specific preparation method, as long as the polymer microspheres can be prepared.
[0118] Taking the preparation of polylactic acid-co-glycolic acid (PLGA) microspheres as an example, the specific preparation method may include the following steps: dissolving the PLGA polymer in a good solvent (e.g., dichloromethane, chloroform, etc.), wherein the mass concentration of the PLGA polymer is 1-20%, preferably 1-10%, and after complete dissolution, the PLGA polymer solution is mixed with an aqueous solution of polyvinyl alcohol (PVA) (the mass concentration of the polyvinyl alcohol is 0.3-3.0%, preferably 1.0-1.5%) to obtain an oil-in-water emulsion. After stirring for several hours, the good solvent is completely volatilized, the polymer solidifies to form micron-sized particles, and then after several times of water washing and centrifugation, the corresponding PLGA microspheres are obtained.
[0119] The present invention firstly performs mineralization treatment on the polymer microspheres to obtain mineralized microspheres; then makes the surface and / or interior of the mineralized microspheres have active ingredients, wherein the active ingredients include metal ions and / or metal nanoparticles, to obtain functionalized microspheres.
[0120] In some specific embodiments, the mineralization treatment includes using simulated body fluid for mineralization treatment to obtain mineralized microspheres. The inventors of the present invention have found that the polymer microspheres can be mineralized by using simulated body fluids, thereby easily depositing or loading active ingredients. Specifically, the polymer microspheres can be suspended in simulated body fluids for mineralization treatment. Specifically, the simulated body fluid can be a SBF solution. The simulated body fluid of the present invention can be purchased commercially or prepared by itself.
[0121] In some specific embodiments, the mineralization time is 6-18 hours, for example, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, etc.; the mineralization temperature is 35-40°C, for example, 36°C, 37°C, 38°C, 39°C, etc. During the mineralization process, it is necessary to stabilize the pH value of the simulated body fluid at 6-7 using an acidic substance.
[0122] In some specific embodiments, the mineralized microspheres are immersed in a functionalization solution for functionalization treatment, so that the surface and / or interior of the mineralized microspheres have active ingredients, and the active ingredients include metal ions and / or metal nanoparticles, to obtain functionalized microspheres; wherein the functionalization solution includes metal salts and / or metal nanoparticles.
[0123] The present invention does not limit the metal salt, and it can be a metal salt commonly used in the art with active functions. Specifically, the metal salt can be a strontium salt, a magnesium salt, a copper salt, an iron salt or a zinc salt. Among them, the strontium salt can be, for example, strontium sulfate, strontium nitrate, strontium chloride, strontium carbonate, etc., the magnesium salt can be magnesium sulfate, magnesium nitrate, magnesium chloride, magnesium carbonate, the copper salt can be copper sulfate, copper nitrate, copper chloride, copper carbonate, the iron salt can be iron sulfate, iron nitrate, iron chloride, iron carbonate, and the zinc salt can be zinc sulfate, zinc nitrate, zinc chloride, zinc carbonate, etc.
[0124] The present invention does not specifically limit the metal nanoparticles, and the metal nanoparticles may be any feasible metal nanoparticles in the art. Specifically, the metal nanoparticles may be silver nanoparticles, gold nanoparticles, copper nanoparticles, iron nanoparticles, and the like.
[0125] In some specific embodiments, in the functionalized solution, the mass concentration of the metal salt is 0.0005-0.1%, for example: 0.001%, 0.003%, 0.005%, 0.008%, 0.01%, 0.02%, 0.05%, 0.08%, etc.; the mass concentration of the metal nanoparticles is 0.0005-0.1%, for example: 0.001%, 0.003%, 0.005%, 0.008%, 0.01%, 0.02%, 0.05%, 0.08%, etc.
[0126] The present invention does not specifically limit the time of immersion, and can be set as needed. Specifically, in the present invention, the immersion time can be 2-6 hours, for example, 3 hours, 4 hours, 5 hours, etc. In order to better obtain functionalized microspheres, magnetic stirring can be used.
[0127] Preparation of composite hydrogel
[0128] In the present invention, the composite hydrogel is obtained by mixing and incubating the functionalized microspheres with the gel product.
[0129] Specifically, the functionalized microspheres can be dissolved in a solvent to obtain a microsphere solution, which is then mixed with a gel product and incubated in an incubator to obtain a composite hydrogel.
[0130] Specifically, in the microsphere solution, the mass volume concentration of the functionalized microspheres is 0.05-5 mg / mL, for example: 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, etc.
[0131] The present invention does not particularly limit the dosage of the gel product, as long as the content of the polymer microspheres can be 0.001-0.1 mg / mL, for example: 0.005 mg / mL, 0.01 mg / mL, 0.03 mg / mL, 0.05 mg / mL, 0.07 mg / mL, 0.09 mg / mL, etc.
[0132] Furthermore, the incubation time can be 10-60min, for example: 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, etc.; the incubation temperature can be 35-40°C, for example: 36°C, 37°C, 38°C, 39°C, etc.
[0133] <Third Aspect>
[0134] The third aspect of the present invention provides a use of the composite hydrogel according to the first aspect of the present invention for preparing a bone repair material. The bone repair material may be any material used for regeneration and reconstruction of bone defects.
[0135] Example
[0136] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0137] Example 1
[0138] Preparation of PLGA microspheres: PLGA (135 mg) (lactic acid to glycolic acid molar ratio of 75:25) (Shandong Pharmaceutical University, China) was dissolved in dichloromethane solution (4.5 mL), mixed with 1% (w / w) polyvinyl alcohol (1.5 mL) (Sigma) solution, and ultrasonicated for 1 min. After complete mixing, a preliminary PLGA mixed solution was obtained. The preliminary PLGA mixed solution was added to 1% (w / w) polyvinyl alcohol solution (50 mL). An oil-in-water emulsion was prepared after 3 minutes using a stirrer. Subsequently, dichloromethane (Yuanye Biotechnology Co., Ltd., China) was stirred with a magnetic stirrer at room temperature for 6 hours. After the dichloromethane was completely volatilized, the PLGA microsphere product was collected by centrifugation at 3000 rpm. The collected PLGA microsphere product was washed 3 times with deionized water, freeze-dried, and stored at 4°C before use.
[0139] Mineralization of microspheres: The PLGA microsphere product was suspended in 10 mL 5×SBF (Solarbio, China), immersed at 37° C. for 12 h, and the pH value of the SBF solution was stabilized at about 6.5 with hydrochloric acid to obtain PLGA mineralized microspheres.
[0140] Loading of AgNPs and Sr 2+ Deposition: 100 mg of PLGA mineralized microspheres were placed in 100 ml of deionized water, 2.7 mg of strontium chloride powder and 2 mg of nanosilver powder were added thereto, magnetically stirred at room temperature for 4 hours, and centrifuged to obtain functionalized microspheres, namely PLGA-Ag-Sr microspheres (P-AS microspheres for short). The functionalized microspheres were washed with deionized water and collected by centrifugation.
[0141] Preparation of SIS gel: Fresh porcine small intestine was cut into pieces of about 10 cm in length, the mesentery was peeled off, and the mucosal layer and serum membrane layer were mechanically scraped to a transparent film. Then, it was defatted with methanol and chloroform (v / v=1:1) for 8 hours and digested with 0.05% trypsin for 8 hours to obtain SIS. After SIS was washed in detergent (a mixture of 0.5% SDS and 0.9% NaCl) for 4 hours, trypsin (0.25 g) was added and magnetically stirred for 24 hours, and SIS pre-gel was obtained after centrifugation. The pH of SIS pre-gel was neutralized to 7.4, and it was placed in an incubator at 37°C for 30 minutes to allow the pre-gel to self-assemble, and SIS gel was obtained.
[0142] Preparation of composite hydrogel: The prepared functionalized microspheres (100 mg) were dissolved in deionized water at a concentration of 1 mg / mL. 10 μL was added to 1 mL of SIS gel and incubated in a 37°C incubator for 30 min to form a composite hydrogel, which was recorded as P-AS-SIS.
[0143] Example 2
[0144] Preparation of PLGA microspheres: PLGA (135 mg) (molar ratio of lactic acid to glycolic acid is 75:25) (Shandong Pharmaceutical University, China) was dissolved in dichloromethane solution (4.5 mL), mixed with 1% (w / w) polyvinyl alcohol (1.5 mL) solution, and ultrasonicated for 1 min. After complete mixing, a preliminary PLGA mixed solution was obtained. The preliminary PLGA mixed solution was added to 1% (w / w) polyvinyl alcohol solution (50 mL). An oil-in-water emulsion was prepared after 3 minutes using a stirrer. Subsequently, dichloromethane (Yuanye Biotechnology Co., Ltd., China) was stirred with a magnetic stirrer at room temperature for 6 hours. After the dichloromethane was completely volatilized, the PLGA microsphere product was collected by centrifugation at 3000 rpm. The collected PLGA microsphere product was washed 3 times with deionized water, freeze-dried, and stored at 4°C before use.
[0145] Mineralization of microspheres: The PLGA microsphere product was suspended in 10 mL 5×SBF (Solarbio, China), immersed at 37° C. for 12 h, and the pH value of the SBF solution was stabilized at about 6.5 with hydrochloric acid to obtain PLGA mineralized microspheres.
[0146] Sr 2+ Deposition: 100 mg of PLGA mineralized microspheres were placed in 100 ml of deionized water, 2.7 mg of strontium chloride powder was added thereto, magnetic stirring was performed at room temperature for 4 hours, and functionalized microspheres, namely PLGA-Sr microspheres (PS microspheres for short) were obtained after centrifugation. The functionalized microspheres were washed with deionized water and collected by centrifugation.
[0147] Preparation of SIS gel: Fresh porcine small intestine was cut into pieces of about 10 cm in length, the mesentery was peeled off, and the mucosal layer and serum membrane layer were mechanically scraped to a transparent film. Then, it was defatted with methanol and chloroform (v / v=1:1) for 8 hours and digested with 0.05% trypsin for 8 hours to obtain SIS. After SIS was washed in detergent (a mixture of 0.5% SDS and 0.9% NaCl) for 4 hours, trypsin (0.25 g) was added and magnetically stirred for 24 hours, and SIS pre-gel was obtained after centrifugation. The pH of SIS pre-gel was neutralized to 7.4, and it was placed in an incubator at 37°C for 30 minutes to allow the pre-gel to self-assemble, and SIS gel was obtained.
[0148] Preparation of pre-gel composite hydrogel: Dissolve the prepared functionalized microspheres (100 mg) in deionized water at a concentration of 1 mg / mL. Take 10 μL and add it to 1 mL of SIS gel, incubate in a 37°C incubator for 30 min to form a composite hydrogel, which is recorded as PS-SIS.
[0149] Example 3
[0150] Preparation of PLGA microspheres: PLGA (135 mg) (lactic acid: glycolic acid = 75:25) (Shandong Pharmaceutical University, China) was dissolved in dichloromethane solution (4.5 mL), mixed with 1% (w / w) polyvinyl alcohol (1.5 mL) solution, and ultrasonicated for 1 minute. After complete mixing, a preliminary PLGA mixed solution was obtained. The preliminary PLGA mixed solution was added to 1% (w / w) polyvinyl alcohol solution (50 mL). An oil-in-water emulsion was prepared by a stirrer after 3 minutes. Subsequently, dichloromethane (Yuanye Biotechnology Co., Ltd., China) was stirred with a magnetic stirrer at room temperature for 6 hours to obtain an oil-in-water-in-oil emulsion. After the dichloromethane was completely volatilized, the PLGA microsphere product was collected by centrifugation at 3000 rpm. The collected PLGA microsphere product was washed 3 times with deionized water, freeze-dried, and stored at 4°C before use.
[0151] Mineralization of microspheres: The PLGA microsphere product was suspended in 5 mL 5×SBF (Solarbio, China), immersed at 37° C. for 12 h, and the pH value of the SBF solution was stabilized at about 6.5 with hydrochloric acid to obtain PLGA mineralized microspheres.
[0152] AgNPs loading: 1 mol / L silver nitrate solution (540 μL) was added to 100 mL of deionized water to obtain a silver nitrate solution. Then, PLGA mineralized microspheres (100 mg) were suspended in the silver nitrate solution and gently stirred at room temperature for 4 hours to obtain functionalized microspheres, namely PLGA-Sr microspheres (PS microspheres for short). The functionalized microspheres were washed with deionized water and collected by centrifugation.
[0153] Preparation of SIS gel: Fresh porcine small intestine was cut into pieces of about 10 cm in length, the mesentery was peeled off, and the mucosal layer and serum membrane layer were mechanically scraped to a transparent film. Then, it was defatted with methanol and chloroform (v / v=1:1) for 8 hours and digested with 0.05% trypsin for 8 hours to obtain SIS. After SIS was washed in detergent (a mixture of 0.5% SDS and 0.9% NaCl) for 4 hours, trypsin (0.25 g) was added and magnetically stirred for 24 hours, and SIS pre-gel was obtained after centrifugation. The pH of SIS pre-gel was neutralized to 7.4, and it was placed in an incubator at 37°C for 30 minutes to allow the pre-gel to self-assemble, and SIS gel was obtained.
[0154] Preparation of pre-gel composite hydrogel: The functionalized microspheres (100 mg) were then dissolved in deionized water at a concentration of 1 mg / mL. 10 μL was added to 1 mL of SIS gel and incubated in a 37°C incubator for 30 min to form a composite hydrogel, which was recorded as PA-SIS.
[0155] Comparative Example 1
[0156] Preparation of PLGA microspheres: PLGA (135 mg) (lactic acid: glycolic acid = 75:25) (Shandong Pharmaceutical University, China) was dissolved in dichloromethane solution (4.5 mL), mixed with 1% (w / w) polyvinyl alcohol (1.5 mL) solution, and ultrasonicated for 1 minute. After complete mixing, a preliminary PLGA mixed solution was obtained. The preliminary PLGA mixed solution was added to 1% (w / w) polyvinyl alcohol solution (50 mL). An oil-in-water emulsion was prepared after 3 minutes using a stirrer. Subsequently, dichloromethane (Yuanye Biotechnology Co., Ltd., China) was stirred with a magnetic stirrer at room temperature for 6 hours. After the dichloromethane was completely volatilized, the PLGA microsphere product was collected by centrifugation at 3000 rpm. The collected PLGA microsphere product was washed 3 times with deionized water, freeze-dried, and stored at 4°C before use.
[0157] Preparation of SIS gel: Fresh porcine small intestine was cut into pieces of about 10 cm in length, the mesentery was peeled off, and the mucosal layer and serum membrane layer were mechanically scraped to a transparent film. Then, it was defatted with methanol and chloroform (v / v=1:1) for 8 hours and digested with 0.05% trypsin for 8 hours to obtain SIS. After SIS was washed in detergent (a mixture of 0.5% SDS and 0.9% NaCl) for 4 hours, trypsin (0.25 g) was added and magnetically stirred for 24 hours, and SIS pre-gel was obtained after centrifugation. The pH of SIS pre-gel was neutralized to 7.4, and it was placed in an incubator at 37°C for 30 minutes to self-assemble to obtain SIS gel.
[0158] Preparation of pre-gel composite hydrogel: Dissolve the prepared PLGA microspheres (100 mg) in deionized water at a concentration of 1 mg / mL. Take 10 μL and add it to 1 mL of SIS gel, incubate in a 37°C incubator for 30 min to form a composite hydrogel, which is recorded as: P-SIS.
[0159] Performance Testing
[0160] 1. Characteristic analysis of composite hydrogel
[0161] 1.1 Characterization of composite hydrogels
[0162] The samples were sputter-coated with platinum (30 mA, 30 s) using a sputter-coater (Polaron E5600, USA), and the morphology of the composite hydrogel and the microspheres were observed using a scanning electron microscope (SEM, JSM-7500F, Japan). Figure 1-3 Elemental mapping was performed under the same parameters as SEM observations with an exposure time of 180 seconds.
[0163] The samples were also analyzed by X-ray energy-dispersive spectroscopy (EDS, Inca X-Max, UK) and recorded at 15 kV. Figure 2 shown.
[0164] The average particle size of the spheroids is estimated to be about 10 μm ( Figure 1 , Figure 2 During the preparation of the microspheres, the biomineralization of the microspheres was completed by immersing the microspheres in SBF, a step that made the surface of the PLGA microspheres rough ( Figure 1 ).
[0165] Figure 2 The SEM image confirms the combination of PLGA and SIS. EDS can detect the silver signal ( Figure 2), where a large amount of AgNPs are deposited on the surface of the microspheres. At the same time, biomineralization causes AgNPs to be loaded on the surface of the PLGA microspheres, and Sr ions are deposited on the surface of the microspheres and then play a role. From the SEM image, the freeze-dried SIS hydrogel is loose and porous, with a certain thickness ( Figure 3 ), which is beneficial to the slow release of drug-loaded components and plays a barrier protection role in the bone defect area.
[0166] 1.2 Ion release test
[0167] The Sr content in the composite hydrogel was determined by inductively coupled plasma optical emission spectrometry (ICP-OES, ICPS-7500, Shimadzu, Japan). 2+ and Ag + The composite hydrogel was placed in 10 mL of PBS buffer (pH 7.2) and incubated at 37 °C with continuous stirring (50 rpm) for 21 days. The total liquid was collected at predetermined time points (1, 3, 5, 7, 9, 11, 13, 15, 19, and 21 days) and the sustained release capacity was tested. At the same time, fresh PBS buffer (10 mL) was added and the release experiment was continued. The results are shown in Figure 2. Figure 4 shown.
[0168] The sustained release ability of the composite hydrogel P-AS-SIS was evaluated by ICP-AES. The release curve of AgNPs ( Figure 4 ) showed that the release rate of AgNPs (P-AS-SIS (Ag)) was faster during the 5th to 15th day, and then the released silver concentration stabilized and reached a plateau of 59.09% ( Figure 4 ). Sr 2+ The release curve of (P-AS-SIS(Sr)) is similar to the release kinetics of AgNPs. The release rate is fast in the first 15 days, and the release rate is basically stable after the 15th day, reaching about 65.88% per day ( Figure 4 ). The above results show that the AgNPs and Sr released by the composite hydrogel 2+ It can continue to play a role in the bone defect area, avoiding the direct introduction of AgNPs and Sr 2+ The sudden release phenomenon caused by this.
[0169] 2. Biocompatibility of composite hydrogel
[0170] Cell viability was detected using a CCK-8 kit (Bestbio, China). BMSCs and RAW264.7 cells were seeded in 96-well plates at 2,000 cells / well and 5,000 cells / well in PA-SIS, PS-SIS, and P-AS-SIS, respectively, with the complete medium supplement group as a blank control. After several days of culture, the optical density (OD) value was measured at 450 nm.
[0171] To further evaluate the cytotoxicity of the samples, BMSCs and RAW264.7 cells were co-cultured with the sample extracts for 3 days. Cell survival was detected using a Calcein-AM / PI kit (Bestbio, China) and observed using a fluorescence microscope (Olympus, Tokyo, Japan).
[0172] Depend on Figure 5 It can be seen that the material needs to have good biocompatibility during application. After co-culture with the gel extract for a period of time, cell proliferation and cell viability were observed by CCK-8 and Calcein-AM / PI staining. Figure 5 A and Figure 5 B shows that the cell viability in each experimental group is good, indicating that the composite hydrogel has no cytotoxicity and can coexist with bone marrow mesenchymal stem cells and RAW264.7 cells.
[0173] 3. Antibacterial test
[0174] PA-SIS, PS-SIS, and P-AS-SIS composite hydrogels (5 mL) were irradiated under UV light for 60 min and then placed in a sterile centrifuge tube containing Dulbecco's modified Eagle's medium (10 mL) (DMEM) and slowly shaken at 120 rpm in a 37°C shaker. The supernatant was collected at specific time points to obtain sample extracts according to experimental requirements. E. coli and S. aureus were adjusted to 10 6 The sample extract was placed in 10 mL of bacterial solution, and the group without sample extract was used as a blank control. After shaking at 37°C for 6 hours, 100 μL of bacterial solution was taken out and inoculated on brain heart infusion (BHI) agar plates for 24 hours. The colonies on the agar plates were observed. The antibacterial results were as follows: Figure 6 B and Figure 6 As shown in C.
[0175] For the inhibition zone test, the composite hydrogel was pressed into thin sheets (50 mg) and compressed into disks (13 mm in diameter and 1 mm in thickness). These disks were placed on the surface of 1.5% agarose gel containing approximately 1×10 7aureus or Escherichia coli, and then incubated at 37°C for 24 hours. Figure 6 As shown in D.
[0176] For the treatment of bone defects, the material also needs to have good antibacterial activity and be able to continue to be antibacterial throughout the defect repair process. S. aureus and E. coli are two common bacteria in surgical procedures and are used to verify the antibacterial properties of composite hydrogels. Bacterial adhesion and biofilm formation are the first key steps for bacterial colonization leading to bone infection. Once a biofilm is formed, bacteria are more likely to attach and difficult to remove. AgNPs are effective against a broad spectrum of bacteria, which is due to the fact that Ag + In addition to releasing Ag, + In addition, AgNPs themselves can also kill bacteria. AgNPs aggregate in pits formed in bacterial cell walls, causing bacterial cell membrane denaturation.
[0177] Depend on Figure 6 It can be seen that after one day of incubation with bacteria, the sample extracts of each group were observed by SEM ( Figure 6 A), the blank control group and PS-SIS group had no antibacterial activity due to the lack of AgNPs, while the PA-SIS group and P-AS-SIS group showed obvious antibacterial effects. The above results indicate that the antibacterial properties of the composite hydrogels depend on the loading of AgNPs. Similarly, the number of colonies in the blank control group and PS-SIS group was significantly higher than that in the PA-SIS group and P-AS-SIS group ( Figure 6 B), the results were statistically significant ( Figure 6 C). Inhibition zone assay ( Figure 6 D) showed that the AgNPs in the PA-SIS group and the P-AS-SIS group had good antibacterial effects, and the inhibitory effect on S. aureus was better than that on E. coli.
[0178] 4. Live / dead cell staining experiment
[0179] The antibacterial analysis of the composite hydrogel was performed by live / dead staining test and inhibition zone test using E. coli and S. aureus. E. coli and S. aureus were incubated in BHI at 37°C for 24 hours, and then their density was diluted to 10 7 CFU / mL, based on absorbance measurement at a wavelength of 600 nm, was used to establish a standard curve.
[0180] The sample extract prepared in the above antibacterial experiment was added to each well of the 96-well tissue culture plate, and then 200 μL of E. coli or S. aureus suspension was added. After the system was incubated at 37°C for 24 hours, SYTO9 / PI staining was performed. Fluorescence images were taken using a confocal laser scanning microscope (CLSM, TCS SP8, Leica) to determine the live / dead state of E. coli or S. aureus. The results are shown in Figure 2. Figure 7 shown.
[0181] Depend on Figure 7 It can be seen that the results of live and dead bacteria staining ( Figure 7 A, Figure 7 B) Consistent with the above experiments, it can be seen that the blank control group and PS-SIS group showed a large number of live bacteria, while it was difficult to see surviving bacteria in the PA-SIS group and P-AS-SIS group. These results further prove that the composite hydrogel containing AgNPs has good antibacterial activity.
[0182] 5. Effect of composite hydrogel on the expression of osteogenic-related factors of bone marrow mesenchymal stem cells
[0183] For the treatment of bone defects, osteogenesis is the key to successful treatment. Therefore, it is necessary to evaluate the osteogenesis of composite hydrogels. The osteogenic differentiation process of bone marrow mesenchymal stem cells stimulated by composite hydrogels is accompanied by the expression of osteogenic genes and related proteins. BMP2, RUNX2, ALP and OPN are typical osteogenesis-related factors. Among them, ALP, as a phosphatase that plays an important role in bone mineralization, is considered to be an early marker of osteogenic differentiation. RUNX2 is expressed in the early stage of osteogenesis and promotes the differentiation of stem cells into osteoblasts, while OPN, as a late bone marker, plays an important role in regulating the growth and formation of bone minerals.
[0184] The ALP activity assay was used to evaluate the effect of the samples on the osteogenic differentiation of bone marrow mesenchymal stem cells. Bone marrow mesenchymal stem cells were cultured in 6-well plates. The culture medium was renewed every 2 days. After 7 days of culture, the ALP activity was measured using a p-nitrophenyl phosphate assay kit (Beyotime, China).
[0185] After 7 days of culture, qRT-PCR was used to detect the expression levels of typical osteogenic genes (RUNX2, OPN, ALP and BMP2) in bone marrow mesenchymal stem cells. The primers of the relevant genes are shown in Table 1 below.
[0186] In the treatment of bone defects, the early stage is mainly a macrophage-mediated inflammatory stage. The phenotype of macrophages is first dominated by M1, producing pro-inflammatory mediators, and then dominated by M2, secreting anti-inflammatory cytokines, leading to the recruitment and activation of osteoblasts into osteogenesis. The introduction of implant materials can enhance osteogenesis by mediating a favorable immune response, or it can lead to failure of bone repair due to an inappropriate immune state. Therefore, the key to successful regeneration of bone tissue is the timely transition between the two phenotypes of macrophages.
[0187] The expression and distribution of osteoblast-related proteins were observed by cell immunofluorescence staining and Western blot analysis. Bone marrow mesenchymal stem cells were cultured for 3 days. BMP2 and ALP (1:200, Abcam, UK) were immunofluorescently stained according to the above steps and observed by CLSM. After 7 days of culture, the expression of osteoblast-related proteins was analyzed by immunoblotting.
[0188] Among them, bone marrow mesenchymal stem cells were collected, cultured and lysed (RIPA / PMSF=100:1), and total proteins were extracted. These proteins were separated by sodium dodecyl sulfate-polyacrylamide electrophoresis (SDS-PAGE) and transferred to polyvinylidene fluoride (PVDF). After blocking with 5% skim milk at room temperature for 1 hour, the composite hydrogel was incubated with BMP2, ALP, RUNX2 and OPN primary antibodies (1:1000, Abcam, UK) at 4°C overnight, and GAPDH (1:1000, Abcam, UK) was used as an internal reference. Then it was incubated with secondary antibodies (1:1000, Beyotime, China) at room temperature for 1 hour, and protein expression was detected with ultrasensitive ECL chemiluminescence reagent. ImageJ v1.8.0 software was used for quantitative analysis of the bands. Figure 8 It can be seen that the mRNA levels of the above osteogenic factors were significantly increased in the PS-SIS group and P-AS-SIS group composite gels ( Figure 8 A). Immunoblotting analysis ( Figure 8 B) also showed the same trend. In RT-PCR detection, osteogenesis-related genes ALP, BMP2, OPN, RUNX2, etc. showed the highest expression in the P-AS-SIS group ( Figure 8 C). ALP and ARS staining ( Figure 8 D) showed that the alkaline phosphatase expression and biomineralization levels of the PS-SIS group and the P-AS-SIS group were higher than those of the blank group and the PA-SIS group.
[0189] Afterwards, the distribution of BMP2 and ALP proteins in BMSC cells was observed using CLSM ( Fig. 9 A and Fig. 9B), in the PS-SIS group and P-AS-SIS group, the green fluorescence of the protein was significantly higher than that in the blank group and PA-SIS group, and more BMSC cells grew in the spheroids. This shows that PLGA microspheres have good biocompatibility. The above results not only show that the composite hydrogel has good biocompatibility, but also that the Sr ions therein can promote osteogenic differentiation.
[0190] 6. Observation of the cytoskeleton and macrophage response to samples
[0191] RAW264.7 cells were seeded on the composite hydrogel surface. After co-culture with the sample for 3 days, it was fixed with 4% paraformaldehyde, permeabilized with 0.5% TritonX-100 for 10 minutes, washed with PBS 3 times, and the cytoskeleton actin and nucleus were stained with rhodamine B-phalloidin and DAPI. The cytoskeleton was observed by CLSM. The results are shown in Fig.10 shown.
[0192] To evaluate the response of macrophages to gene levels in sample extracts, M1-related genes TNF-α, IL-1β and M2-related genes TGF-β, IL-10 were analyzed using qRT-PCR, with GAPDH as an internal reference gene. Specifically, RAW264.7 cells were seeded in 6-well plates at a density of 50,000 cells / well. Total RNA was extracted after 3 days of incubation, and cDNA was synthesized using a reverse transcription kit (Promega, USA). GoTaq qPCR master mix (Promega, USA), primers, and cDNA were added to a 96-well PCR plate. Then, qRT-PCR analysis was performed on a Roche LC480II system (Roche, Switzerland).
[0193] After 3 days of co-culture with the samples, surface markers of iNOS and CD206 were detected by immunofluorescence. iNOS (1:200, Abcam, UK) and CD206 (1:200, Proteintech, USA) were used as primary antibodies and incubated with cells overnight at 4°C. After washing with PBS buffer solution, cells were incubated with Cy3-conjugated secondary antibodies (1:1000, Abcam, UK) at room temperature for 1 hour, cell nuclei were stained with DAPI, and fluorescence images were obtained using CLSM.
[0194] The macrophages involved in the inflammatory response underwent morphological changes, with M1 macrophages being round and M2 macrophages being spindle-shaped. Each experimental group and material was cultured for 3 days, and then immunofluorescence staining and cytoskeleton staining were performed. It can be seen that the cell morphology of the blank group and the PA-SIS group was mostly round, while spindle cells were seen in the PS-SIS group and the P-AS-SIS group ( Fig.10A). In addition, M1 macrophages mainly secrete pro-inflammatory factors such as iNOS, IL-6, IL-1β, and TNF-α, while M2 macrophages produce TGF-β and IL-10. Gene expression results showed ( Fig.10 B), compared with the blank group and PA-SIS group, the expressions of IL-1β and TNF-α were significantly downregulated, and the expressions of TGF-β and IL-10 were increased in the PS-SIS and SIS groups.
[0195] iNOS and CD206 are representative surface markers of M1 and M2 macrophages. CLSM results showed that the introduction of Sr 2+ The fluorescence of M2 phenotype protein was stronger than that of blank group and PA-SIS group, and the fluorescence of M1 surface marker was weaker. 2+ Can promote macrophage polarization ( Fig.10 C).
[0196] The primers of the relevant genes in the experiment of the present invention are shown in Table 1:
[0197] Table 1
[0198]
[0199] 7. Repair effect of composite hydrogel on infected skull defects
[0200] Male Sprague-Dawley (SD) rats (250-300 g, 5-6 weeks old) were purchased from Beijing Weitong Lihua Experimental Animal Technology Co., Ltd. (Beijing, China), and the animal experiments were approved by the Animal Ethics and Welfare Committee. A total of 24 male SD rats were required for this study and randomly divided into four groups (n=3): blank group, PA-SIS, PS-SIS and P-AS-SIS. Rats were anesthetized with 10% chloral hydrate (100 g / 0.3 mL). The principle of aseptic treatment was strictly followed during the operation. An 8 mm circular defect was formed in the central area of the skull. The gel was then injected into the bone defect, and the group without gel served as a blank control. Finally, the skin was sutured.
[0201] The rats were killed 3 months after surgery and the skulls were removed. After fixation with 4% paraformaldehyde solution for 48 hours, the skulls were reconstructed using Micro-CT scanning (Sky Scan 1276, Germany). CT-vox software was used to view the images, and CT An software was used to perform statistical analysis on the bone volume fraction (BV / TV) of the region of interest (ROI).
[0202] The skull specimens were decalcified, dehydrated, embedded, and cut into 5 μm thick sections, which were then stained with hematoxylin-eosin (H&E) and Masson's trichrome, respectively.
[0203] The sections were immunohistochemically stained for the expression of cyanate and COL-1 (1:200, Abcam, UK). The sections were incubated with the primary antibody at 4°C overnight and then treated with the secondary antibody at room temperature for 1 hour. Subsequently, the sections were incubated with 3,3-diaminobenzidine (DAB). An inverted microscope (Olympus, Japan) was used to observe and acquire images. Fig.11 shown.
[0204] The effects of each group of composite hydrogels on osteogenesis in rats were observed by establishing border bone defects in rats. Micro-CT images showed that new bone formation developed from the defect edge to the center ( Fig.11 A). These cases had a long time after surgery, and a large amount of new bone formation was found in the PS-SIS group and the P-AS-SIS group. At 12 weeks after surgery, the BV / TV ratio was the lowest in the blank control group, and the highest in the PS-SIS group and the P-AS-SIS group ( Fig.11 B), indicating that the PS-SIS group and the P-AS-SIS group had the highest degree of bone regeneration. In addition, there was a small amount of new bone formation in the PA-SIS group ( Fig.11 A), this may be because SIS also has certain osteoinductive properties.
[0205] Mineralization is the main process of osteoblasts promoting bone formation. Collagen can also start and spread mineralization as a template. The content of collagen plays an important role in the process of new bone formation. H&E staining and Masson staining were used to observe the growth of collagen and new bone tissue and the infiltration of lymphocytes. The results are as follows Fig.11 C and Fig.11 As shown in D, it can be seen that the defect area in the blank group and PA-SIS group was mainly composed of fibrous tissue, and there was no obvious sign of new bone formation. In the PS-SIS group and P-AS-SIS group, a large amount of collagen components were present. In addition, no obvious lymphocyte infiltration was observed in any experimental group, indicating that no inflammatory response occurred during the new bone formation process. Immunohistochemistry was used to detect the expression of osteocalcin (cyanate) and type I collagen (COL1) ( Fig.11 E). The staining of the blank group and the PA-SIS group was not obvious, while the expression of cyanate and COL1 in the PS-SIS group and the P-AS-SIS group was high.
[0206] The above results show that the composite hydrogel can effectively promote the formation of new bone in the defect area and can be used as an implant material for bone tissue engineering, with good application prospects.
[0207] In summary, by using AgNPs and Sr 2+The SIS hydrogel was modified and slowly administered via PLGA microspheres. The P-AS-SIS composite hydrogel increased the expression of osteoblast-related genes BMP2, RUNX2, ALP, and OPN, and promoted the polarization of macrophages toward the M2 phenotype. This study evaluated the performance of the material from the perspective of the bone immune microenvironment and provided new ideas for the treatment of bone defects.
[0208] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0209] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A composite hydrogel, characterized in that: include: A carrier matrix, wherein the carrier matrix is derived from a degradable biomaterial, and the degradable biomaterial contains collagen; as well as, polymer microspheres, the polymer microspheres being loaded on the surface and / or inside of the carrier matrix; and, The polymer microspheres have active ingredients on their surfaces and / or inside, and the active ingredients include metal ions and / or metal nanoparticles.
2. The composite hydrogel according to claim 1, characterized in that The carrier matrix is obtained by hydrolyzing the degradable biomaterial with a protease; preferably, the degradable biomaterial contains collagen, and more preferably, the degradable biomaterial contains small intestinal submucosal material.
3. The composite hydrogel according to claim 1 or 2, characterized in that: The average particle size of the polymer microspheres is 1-100 μm; Preferably, the polymer microspheres are derived from one or a combination of two or more of gelatin microspheres, polylactic acid microspheres, polycaprolactone microspheres, polyglycolic acid microspheres, polymethyl methacrylate microspheres, and polylactic acid-glycolic acid copolymer microspheres.
4. The composite hydrogel according to any one of claims 1 to 3, characterized in that Based on the total volume of the carrier matrix, the content of the polymer microspheres is 0.001-0.1 mg / mL.
5. The composite hydrogel according to any one of claims 1 to 4, characterized in that The metal ions include one or a combination of two or more of strontium ions, magnesium ions, copper ions, iron ions and zinc ions; The metal nanoparticles include one or a combination of two or more of silver nanoparticles, gold nanoparticles, copper nanoparticles, and iron nanoparticles.
6. A method for preparing the composite hydrogel according to any one of claims 1 to 5, characterized in that: The method comprises the steps of loading the polymer microspheres on the surface and / or inside of the carrier matrix; Preferably, the preparation method comprises the following steps: The degradable biomaterial is hydrolyzed by protease to obtain a pre-gel; Adjusting the pH value of the pregel to 6-8 to allow the pregel to self-assemble to obtain a gel product; Performing mineralization treatment on the polymer microspheres to obtain mineralized microspheres; The surface and / or interior of the mineralized microspheres are provided with active ingredients, wherein the active ingredients include metal ions and / or metal nanoparticles, to obtain functionalized microspheres; The functionalized microspheres are mixed with the gel product and incubated to obtain a composite hydrogel.
7. The preparation method according to claim 6, characterized in that: The hydrolysis treatment lasts for 6-18 hours. Preferably, before the hydrolysis treatment, a step of washing the degradable biomaterial with a detergent is also included.
8. The preparation method according to claim 6 or 7, characterized in that: The mineralization treatment includes using simulated body fluid to perform mineralization treatment on the polymer microspheres to obtain mineralized microspheres; more preferably, the mineralization treatment time is 6-18 hours, and the mineralization treatment temperature is 35-40°C.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The mineralized microspheres are immersed in a functionalization solution for functionalization treatment, so that the surface and / or the interior of the mineralized microspheres have active ingredients, and the active ingredients include metal ions and / or metal nanoparticles, to obtain functionalized microspheres; wherein the functionalization solution includes metal salts and / or metal nanoparticles; preferably, the immersion time is 2-6 hours; More preferably, in the functionalized solution, the mass concentration of the metal salt is 0.0005-0.1%, and the mass concentration of the metal nanoparticles is 0.0005-0.1%.
10. Use of the composite hydrogel according to any one of claims 1 to 5 for preparing bone repair materials.